-20+9h=-3h+12+10h

Simple and best practice solution for -20+9h=-3h+12+10h equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -20+9h=-3h+12+10h equation:


Simplifying
-20 + 9h = -3h + 12 + 10h

Reorder the terms:
-20 + 9h = 12 + -3h + 10h

Combine like terms: -3h + 10h = 7h
-20 + 9h = 12 + 7h

Solving
-20 + 9h = 12 + 7h

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '-7h' to each side of the equation.
-20 + 9h + -7h = 12 + 7h + -7h

Combine like terms: 9h + -7h = 2h
-20 + 2h = 12 + 7h + -7h

Combine like terms: 7h + -7h = 0
-20 + 2h = 12 + 0
-20 + 2h = 12

Add '20' to each side of the equation.
-20 + 20 + 2h = 12 + 20

Combine like terms: -20 + 20 = 0
0 + 2h = 12 + 20
2h = 12 + 20

Combine like terms: 12 + 20 = 32
2h = 32

Divide each side by '2'.
h = 16

Simplifying
h = 16

See similar equations:

| 4x+38=7x+8 | | H/4=5 | | 8x+6x-69=92-9x | | -12-11z=8-10z | | 3sinx+7=0.5cosx | | X^2-14x+48=48 | | 8=(2x+10)(2x+8) | | 7+2y=y-3 | | -1+9+m=-10-5m | | -0.1001x+100000*ln(x+1)-50.0001=0 | | m-16=2 | | e=125(-122) | | 1/7-11/14 | | -6j-2=-7j+7 | | -2=y-3 | | -2t+4=-t | | 4x-3(5x+7)-11=11+4(-3x-2)+2x | | -2x=y-3 | | 2(3x-3)-2(2m+4)= | | 2c+8=-7c-10 | | t^2/2t | | 175m-75+57900=61200-200 | | 9u-7=3u+5 | | 3ln(3x-4)=8 | | -3-y=1 | | -3-7=1 | | 4x^3-6=0 | | -4g=-5g-4 | | 4/5-1/5=2/5n | | 4/5-1/5=2/5 | | 2d^2-6d=10 | | (4z+6)+x+2y+106=180 |

Equations solver categories